2006
DOI: 10.1183/09059180.00010105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphology of compensatory lung growth

Abstract: Compensatory lung growth is defined by the absolute increases in the quantity of functioning lung tissue in response to injury and/or disease, leading to a positive impact on functional outcome. The pneumonectomy model is used as an example to illustrate the salient features of compensatory growth and the specific considerations in its morphological quantification, including techniques of sampling and analysis, resolution of ultrastructural details, selection of markers for measurement, and interpretation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…Studies in young and adult dogs undergoing right lung PNX revealed that growth of alveolar septa is characterised by an initial disproportionate increase in interstitial cells and matrix by nearly 3.6-fold, whereas epithelial and endothelial cells increase ,2-fold compared with control lungs [14,38]. Later on, proportions of septal cells gradually normalised resulting in a final 2-fold increase in all compartments relative to age-matched control lungs, and a normal harmonic mean septal barrier thickness and improved lung diffusing capacity were achieved [9].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies in young and adult dogs undergoing right lung PNX revealed that growth of alveolar septa is characterised by an initial disproportionate increase in interstitial cells and matrix by nearly 3.6-fold, whereas epithelial and endothelial cells increase ,2-fold compared with control lungs [14,38]. Later on, proportions of septal cells gradually normalised resulting in a final 2-fold increase in all compartments relative to age-matched control lungs, and a normal harmonic mean septal barrier thickness and improved lung diffusing capacity were achieved [9].…”
Section: Discussionmentioning
confidence: 94%
“…As highlighted recently [9], the PNX model has several great advantages: it mimics the loss of functional lung units seen in destructive lung diseases; the loss of tissue is well defined and reproducible; the remaining lung is normal; and compensatory responses can be quantified without difficulty.…”
mentioning
confidence: 99%
“…Realising that we could not adequately cover some areas that significantly rely on quantitative morphology, we were happy that Connie C.W. Hsia, Prescott G. Woodruff, and Anh L. Innes agreed to contribute with their expertise in compensatory lung growth [26] and in the study of bronchial biopsies [27], an approach that directly relates stereology to the study of human disease. Although some of the major lung diseases, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly suitable for the lung, as it can be applied to structures that are inhomogeneous or cannot be assumed to be homogeneous. Despite this and the subsequent developments made towards obtaining unbiased quantitative data of inhomogeneous structures, such as lung parenchyma and the bronchial tree, stereology has been used less in pulmonary research than in other fields.In recent years, the European Respiratory Society (ERS) has organised two courses dedicated to quantitative morphology in pulmonary research, followed by a series of articles in one issue of the European Respiratory Review which offered insight into the theoretical principles and practical applications of design-based stereology to graduate students and scientists [7][8][9][10][11][12][13]. …”
mentioning
confidence: 99%
“…In recent years, the European Respiratory Society (ERS) has organised two courses dedicated to quantitative morphology in pulmonary research, followed by a series of articles in one issue of the European Respiratory Review which offered insight into the theoretical principles and practical applications of design-based stereology to graduate students and scientists [7][8][9][10][11][12][13].…”
mentioning
confidence: 99%